(untitled) (Research, Society and Development, 2021)
Lead is a non-essential toxic metal found in several chemical forms, therefore, it can cause air, land and water pollution. The main source of lead is due to anthropic action, through the use of lead-based ammunition, fishing, fuel, mining, waste incineration and industrial activity. The purpose of this review is to demonstrate current knowledge about the sources of lead contamination, the clinical signs and injuries observed in wild birds, diagnosis and treatment, impacts on biodiversity and prevention measures. In order to carry out the study, an article search was used in the scientific databases PubMed, the portal of CAPES, SciELO and Google Scholar journals, in the period from 2015 to 2020. From the studies listed, it was observed that animals are frequently found with subclinical or clinical changes, or even dead in their natural habitats. The literature states that the effects of lead in the body vary according to the dose, time of exposure and route of intoxication, therefore, the consequences on the health of wild birds are numerous. It was concluded that the replacement of lead by other components, changes in regulations and awareness of its disposal, result gains in nature conservation and improvement of biodiversity.